The Role of Citizenship in Enhancing Societal Security in Light of the Current Media Developments - Kliouat, Said; Chettab, Kamel (Journal of Legal Studies and Researches, 2021)
The transformations that the world is witnessing casts a shadow over the concept of citizenship. Citizenship is based on an awareness that must be carried out with the intended education supervised by the state, through which the individual is introduced to the concepts and characteristics of citizenship. This participates in achieving the goals of education for citizenship and contributes to shaping the citizen’s personality and the collective identity of the nation’s cultural, social, and philosophical.